Che fine ha fatto la psichiatria? Crisi di interesse, voglia di formazione e nuove sfide - Bensi, Marco; Fagioli, Marcella; Fiori Nastro, Paolo (Il sogno della farfalla, 2012)
The aim of this article is to describe the current crisis of psychiatry’s scientific credibility. A review of the literature points to a lack of identity characterizing this discipline and giving rise to many contrasting schools of thought. A fall in the request for specialist training and the high number of drop-outs during the professional training period testify to the fact that there is a crisis of credibility. This phenomenon is attributed to a lack of prestige afflicting psychiatry and to a poor consideration of the current diagnostic and therapeutic tools. Many authors suggest giving more importance to the human qualities of the psychiatrist and resuscitating psychopathology as a way of coping with this situation. The Authors believe that a reconsideration of psychodynamic psychotherapy is a key factor in solving this crisis provided that it proves its efficacy in order not to be excluded from scientific debate.